Overexpression of ABCG2 Confers Resistance to MLN7243, a Ubiquitin-Activating Enzyme (UAE) Inhibitor - Wu, Zhuo-Xun; Yang, Yuqi; Wang, Jing-Quan; Narayanan, Silpa; Lei, Zi-Ning; Teng, Qiu-Xu; Zeng, Leli; Chen, Zhe-Sheng (Frontiers in Cell and Developmental Biology, 2021)
Overexpression of ATP-binding cassette transporter superfamily G member 2 (ABCG2), is known as a major mechanism mediating multidrug resistance (MDR) in cancer cells. MLN7243 is a small-molecule ubiquitin activating enzyme inhibitor currently under clinical investigation. The aim of the current study is to determine if MLN7243 is a substrate of MDR-related ABCG2 transporter. Our results showed that cancer cells overexpressing ABCG2 transporter were resistant to MLN7243 compared to the parental cells, while knockout of ABCG2 gene or pharmacological inhibition of ABCG2 efflux function completely reversed the drug resistance. Unexpectedly, the endogenous low expression of ABCG2 is sufficient to confer cancer cells resistance to MLN7243. The ABCG2 ATPase assay and HPLC assay suggested that MLN7243 can significantly stimulate ABCG2 ATPase activity and be pumped out from ABCG2-overexpressing cells by ABCG2. The docking analysis also implied that MLN7243 binds to ABCG2 drug-binding pocket with optimal binding affinity. However, MLN7243 did not competitively inhibit the efflux of other ABCG2 substrate drugs, indicating it may not serve as an MDR reversal agent. In conclusion, our study provides direct in vitro evidence to show that MLN7243 is a potent ABCG2 substrate., If our results can be translated to humans, it suggests that combining MLN7243 with ABCG2 inhibitors may enhance the anticancer efficacy for patients with high tumor ABCG2 level.